2020
DOI: 10.1007/s10342-020-01320-5
|View full text |Cite
|
Sign up to set email alerts
|

Cutting duration and performance parameters of a harvester’s sawing unit under real working conditions

Abstract: Amongst all the working elements of single grip harvesters, the working elements of felling and processing play an important role within the cut-to-length (CTL) harvester’s working phases. This includes the felling cutting and cross-cutting of stems within the felling and processing operation. The detailed investigation of such individual machine activities may help to analyse and improve the performance of forest machines. The objective of this study was to investigate the cutting duration and other performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In their study, tree delimbing accounted for more than 40% of the cycle time. A recent study by Prinz et al (2020) has shown that effective cutting may take as little time as milliseconds, depending on the diameter at which the cuts are performed.…”
Section: Nl Nc Nfmentioning
confidence: 99%
“…In their study, tree delimbing accounted for more than 40% of the cycle time. A recent study by Prinz et al (2020) has shown that effective cutting may take as little time as milliseconds, depending on the diameter at which the cuts are performed.…”
Section: Nl Nc Nfmentioning
confidence: 99%
“…The harvester head's main function and power-consuming functions, chainsaw, and feeding roller drive are hydraulically operated for the time being and will be for quite some years to come and therefore, using a hydraulic energy storage system such as a high-pressure accumulator is advantageous in terms of minimizing energy conversions. As the CTL forest harvester is a critical piece of equipment in this kind of forestry, its work cycle has been studied in time studies [9] as well as performance evaluations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out in different parts of the world to check the performance of single-grip harvesters and processors in forest operations, with the aim to provide an informed ground on equipment capabilities as a baseline for its selection and use in operations, performance modelling and cost estimation [13][14][15][16][17][18][19]. Recently, important steps were taken to improve our understanding on the human-machine interaction [20], fine-scale performance of process mechanics [21] and human exposure to harmful factors [22]. However, mechanized tree processing at the landing was less addressed by scientific studies, and work organization and operational environment in such work places are different from those typically found in the forest stands.…”
Section: Introductionmentioning
confidence: 99%